2018
DOI: 10.1186/s12998-018-0212-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pain knowledge, attitudes and beliefs of osteopathy students after completing a clinically focused pain education module

Abstract: BackgroundChronic pain is a substantial burden on the Australian healthcare system with an estimated 19.2% of Australians experiencing chronic pain. Knowledge of the neurophysiology and multidimensional aspects of pain is imperative to ensure health professionals apply a biopsychosocial approach to pain. Questionnaires may be used to assess learner changes in neurophysiology knowledge and beliefs and attitudes towards pain after education interventions.The aim of this study was to evaluate changes in pain neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
1
5
2
Order By: Relevance
“…This research was in line with Greenberg (2013) revealed that the printed module could significantly increase students' cultural knowledge seen from changes in the average pretest score to posttest average of 8.6 to 19.94. This result was also in line with Fitzgerald et al (2018) revealed that the clinically focused pain modules could significantly improve students' knowledge about neurophysiology of pain with a p-value < .001.…”
Section: Knowledge Of Transcultural Nursingsupporting
confidence: 86%
See 1 more Smart Citation
“…This research was in line with Greenberg (2013) revealed that the printed module could significantly increase students' cultural knowledge seen from changes in the average pretest score to posttest average of 8.6 to 19.94. This result was also in line with Fitzgerald et al (2018) revealed that the clinically focused pain modules could significantly improve students' knowledge about neurophysiology of pain with a p-value < .001.…”
Section: Knowledge Of Transcultural Nursingsupporting
confidence: 86%
“…The use of more concrete learning media such as direct experience, the message or information provided by educators to students will be conveyed well. (Arsyad, 2016) also states that changes in attitude could occur because of interactions between new and previous experiences. Personal direct experience gives a stronger influence than indirect experience (Wawan & Dewi, 2014).…”
Section: Attitude Of Transcultural Nursingmentioning
confidence: 99%
“…One study in Australia supported these results per post-design research to assess the effect of a focused educational pain management module to improve the attitude, knowledge, and beliefs among health care workers. After 12 weeks of clinical education, the result showed significant improvement in the knowledge, attitude, and beliefs among health care workers towards pain management, the instrument used in the study Neurophysiology of Pain (NPQ) Questionnaire and Health Care Providers Pain and Impairment Relationship scale (HC-PAIRS) (Fitzgerald et al, 2018). Lack of studies investigates the mediating effect of modelbased learning on nurses' attitudes and pain management awareness among nurses during the COVID 19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This has been reported as a crucial factor in the pain becoming chronic and could limit the efficacy of therapeutic interventions [37,38]. The NPQ has been used in several educational studies to assess the understanding of health undergraduate students regarding pain neurophysiology [39][40][41][42].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…osteopathy students [40], health care final-year students [54] and osteopaths [14]. A validated version of a 19-item questionnaire was proposed in French in 2015 [38].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%